The Difference the Body Makes: The Teacher's Presence Online and Offline - Carina Henriksson (University of Windsor, 2006)
This paper examines the question: what is the experience of meeting online and how does it differ from ordinary classroom situations? Drawing from personal experience, the author explores possible experiences of existing in virtual space and time. How do people meet, get to know each other and, interact in a pedagogical situation? Her experience as an online student made her to seriously reflect on the experiential nature of the computer-mediated encounter. But, it was not until she happened to participate in a workshop offered by the same teacher that the contrasts began to take shape for her. If there is a difference between online and offline meetings, what is it that makes the difference? Online communication could, just as face-to-face meetings, create feelings of closeness, and friendship; from the other-as-a-text on the screen, we subjectively create the other-as-an-idea, an idea that might be perceived as the real other. But is it? What reality is for real? What is the nature of the relationship established between body-less persons on line, and what difference does the body make in a face-to-face meeting?